Behaviour of different bioactive glasses incorporated in polydimethylsiloxane endodontic sealer. Issue 2 (February 2021) - Hoikkala, Niko-Pekka J.; Siekkinen, Minna; Hupa, Leena; Vallittu, Pekka K.
Abstract: Objectives: The aim of this study was to analyze the behavior of different bioactive glass fillers (BAGs) embedded in a polydimethylsiloxane matrix of an endodontic sealer. Methods: Three different endodontic sealers were fabricated using S53P4, 45S5 and 18−06 glass fillers. Endodontic sealer Guttaflow Bioseal consisting of polydimethylsiloxane (PDMS) matrix was used as base of the experimental sealers. Behaviors of different glass fillers leaching from polymer matrix was studied in vitro for 14 days by measuring static ion dissolution profiles of Si, Na, Ca and P -ions. In addition, pH of the simulated bodyfluid (SBF) was monitored during the 14 days and all the sealer samples was examined with SEM/EDX analysis on the surface. Identical but non-glass filler containing polydimethylsiloxane-based sealer was used as a control material. Results: By the time point of 24 h sealer with 45S5 had released twice as much of Si-ions compared to sealer with S53P4. No statistical differences of Na, Ca and P -ions dissolution were observed in the first 168 h for any groups whereas concentrations of Ca and P -ions decreased with 45S5 significantly after 336 h. Highest pH was measured for sealers with glass filler 45S5 and S53P4 (7.64–7.65). Visible mineral precipitation was observed only on sealer surfaces after 336 h' time period with groups of 45S5 and S53P4. However, presence of calcium and phosphorus oxides was confirmed only with 45S5. Significance: Bioactive glass type 45S5 outperforms S53P4 and 18−06 by acting more dynamically in vitro set-up